Positive selection in East Asians for an EDAR allele that enhances NF-kappaB activation. - Jarosław Bryk (Public Library of Science (PLoS), 2008)
Genome-wide scans for positive selection in humans provide a promising approach to establish links between genetic variants and adaptive phenotypes. From this approach, lists of hundreds of candidate genomic regions for positive selection have been assembled. These candidate regions are expected to contain variants that contribute to adaptive phenotypes, but few of these regions have been associated with phenotypic effects. Here we present evidence that a derived nonsynonymous substitution (370A) in EDAR, a gene involved in ectodermal development, was driven to high frequency in East Asia by positive selection prior to 10,000 years ago. With an in vitro transfection assay, we demonstrate that 370A enhances NF-kappaB activity. Our results suggest that 370A is a positively selected functional genetic variant that underlies an adaptive human phenotype.